2018
DOI: 10.1016/j.neuron.2018.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Caldendrin Directly Couples Postsynaptic Calcium Signals to Actin Remodeling in Dendritic Spines

Abstract: Compartmentalization of calcium-dependent plasticity allows for rapid actin remodeling in dendritic spines. However, molecular mechanisms for the spatio-temporal regulation of filamentous actin (F-actin) dynamics by spinous Ca-transients are still poorly defined. We show that the postsynaptic Ca sensor caldendrin orchestrates nano-domain actin dynamics that are essential for actin remodeling in the early phase of long-term potentiation (LTP). Steep elevation in spinous [Ca] disrupts an intramolecular interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 47 publications
3
97
0
Order By: Relevance
“…n = 17 dendritic segments of 12 cells in three independent cultures. E Representative kymograph from a DIV16 hippocampal neuron expressing PEX-GFP-KIF17 before and after LatA treatment (5 lM) (see also Fig EV4C-E spine synapses, the role and organization of the actin cytoskeleton at shaft synapses have not yet been addressed (Bosch et al, 2014;Konietzny et al, 2017;Mikhaylova et al, 2018). Using pharmacological approaches, we found that the actin mesh consisted of both branched and longitudinal filaments.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…n = 17 dendritic segments of 12 cells in three independent cultures. E Representative kymograph from a DIV16 hippocampal neuron expressing PEX-GFP-KIF17 before and after LatA treatment (5 lM) (see also Fig EV4C-E spine synapses, the role and organization of the actin cytoskeleton at shaft synapses have not yet been addressed (Bosch et al, 2014;Konietzny et al, 2017;Mikhaylova et al, 2018). Using pharmacological approaches, we found that the actin mesh consisted of both branched and longitudinal filaments.…”
Section: Discussionmentioning
confidence: 97%
“…We found that the majority was spread over the dendritic shaft and is positive for excitatory but not inhibitory synaptic markers, and that their size correlates with the presence of homer1. In comparison with spine synapses, the role and organization of the actin cytoskeleton at shaft synapses have not yet been addressed (Bosch et al , ; Konietzny et al , ; Mikhaylova et al , ). Using pharmacological approaches, we found that the actin mesh consisted of both branched and longitudinal filaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their turnover rate, actin filaments can be divided into dynamic and stable pools and based on the morphology described as linear or branched filaments. The controlled assembly and tread milling of F‐actin are essential for plasticity and stability of synapses (MacGillavry et al, ; Mikhaylova et al, ; Mundhenk, Fusi, & Kreutz, ; Stefen et al, ). Importantly, a plethora of actin nucleation factors, severing, and capping proteins are involved in filament formation and regulation of filament stability (Hotulainen & Hoogenraad, ).…”
Section: Synaptic Actin Cytoskeletonmentioning
confidence: 99%
“…In the proximity of the synaptic membrane, cortactin recruits the Arp2/3 complex via N‐WASP and promotes formation of new actin branches (Helgeson & Nolen, ). At the spine base, caldendrin keeps cortactin in an active conformation and protects F‐actin against cofilin‐induced severing (Mikhaylova et al, ). In line with these findings, the stable pool of spinous actin is no longer preserved in caldendrin deficient mice.…”
Section: Synaptic Actin Cytoskeletonmentioning
confidence: 99%